Sab is differentially expressed in the brain and affects neuronal activity - Sodero, Alejandro Omar (2017)
Fil: Sodero, Alejandro Omar. Florida International University. Herbert Wertheim College of Medicine. Department of Cellular Biology and Pharmacology; Estados Unidos